Preparation of magnesium oxysulfate cement using magnesium-rich byproducts from the production of lithium carbonate from salt lakes. (30th May 2018) - Wu, Chengyou; Chen, Cong; Zhang, Huifang; Tan, Yongshan; Yu, Hongfa
Highlights: Low-cost magnesium oxysulfate (MOS) cement prepared using magnesia. Mg-residue calcination from LiCO3 production from salt lake brine produced magnesia. Setting time, strength, hydration mechanism and products, and microstructure studied. Two methods to obtain MOS cement with high early and long-term strengths have been studied. Abstract: Low-cost magnesium oxysulfate (MOS) cement was prepared using magnesia derived from the calcination of magnesium-residue from the production of LiCO3 from salt lake brine. Setting time, mechanical strength, hydration mechanism, hydration products and microstructure of this MOS cement were determined. MOS cement prepared with magnesia after calcination at low temperatures and high molar ratio of a-MgO/MgSO4 was found to harden rapidly but the later-stage strength decreased. However, partial replacement of magnesia obtained from the calcination of magnesium-rich residues by pure light burned magnesia and addition of 5·1·7 phase seed crystals are viable strategies for obtaining MOS cement with improved properties.